Global Changes in Higher Education: Post-Covid Times - J. P. Bayer; N. A. Churaev (Управленческое консультирование)
In this article we talk about education as a global phenomenon that includes many actors with their own political interests. In this regard, the question of the anthropological component of modern education, including in the international context, arises extremely sharply: what kind of person is formed by the new global education, to whom it applies, and what values it forms. Main trends in global education policy are defined. The formation of a global educational policy has not yet been completed, and the pandemic of coronavirus infection has brought both positive and negative aspects. We name both of them: the advantages and disadvantages of pandemic situation that shifted the global higher education into the different format. Also, we make the forecast on further higher education development.